1994
DOI: 10.1523/jneurosci.14-03-01563.1994
|View full text |Cite
|
Sign up to set email alerts
|

ATP-evoked increases in intracellular calcium in neurons and glia from the dorsal spinal cord

Abstract: Fund. M.W.S. is an MRC Scholar. We thank Drs. J. F. MacDonald and Y. De Koninck for critical reading of the manuscript, and Ms. Kathleen Downie for assistance preparing the manuscript. We gratefully acknowledge Dr. J. Cobby at Bayer Canada Inc. for providing suramin. Ms. Lise Aasheim participated in some of the experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
128
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(138 citation statements)
references
References 70 publications
10
128
0
Order By: Relevance
“…8G). Using fura-2 calcium imaging calibration kit (Invitrogen), we estimated that the resting intracellular Ca 2ϩ of astrocytes is 75 Ϯ 5 nM (n ϭ 24), and 348 Ϯ 30 nM (n ϭ 24) after ATP stimulation, similar to a previous report by Salter and Hicks (1994). Will ATP-induced Ca 2ϩ increase affect the dynamin-independent endocytosis in astrocytes?…”
Section: Atp Regulation Of the Dynamin-independent Endocytosis In Astsupporting
confidence: 78%
“…8G). Using fura-2 calcium imaging calibration kit (Invitrogen), we estimated that the resting intracellular Ca 2ϩ of astrocytes is 75 Ϯ 5 nM (n ϭ 24), and 348 Ϯ 30 nM (n ϭ 24) after ATP stimulation, similar to a previous report by Salter and Hicks (1994). Will ATP-induced Ca 2ϩ increase affect the dynamin-independent endocytosis in astrocytes?…”
Section: Atp Regulation Of the Dynamin-independent Endocytosis In Astsupporting
confidence: 78%
“…Previous in vitro studies have shown that activation of purinergic receptors triggers astrocytic Ca 2+ transients (17)(18)(19). We hypothesized that Ca 2+ signals elicited during edema formation depend-at least in part-on ATP release from swollen astrocytes.…”
Section: Discussionmentioning
confidence: 94%
“…Intracellular administration of Src40-49 reduced the NMDAR component of the miniature excitatory post-synaptic currents 20 in cultured dorsal horn neurons (Fig. 1c), neurons in which NMDARs are tonically upregulated by Src 14,21,22 .…”
Section: Constructing a Src-nmdar Uncoupling Peptide For Use In Vivomentioning
confidence: 92%
“…Whole-cell recordings were made from cultured dorsal horn neurons as described 20 . Src (40)(41)(42)(43)(44)(45)(46)(47)(48)(49) or sSrc (40)(41)(42)(43)(44)(45)(46)(47)(48)(49) were added to the intracellular solution for a final concentration of 0.015 mg ml −1 .…”
Section: Electrophysiological Recordingsmentioning
confidence: 99%